Healthcare Supply Chain Disruption Risks - Ahmad, Fatima Wisam (2022)
A Master of Science thesis in Engineering Systems Management by Fatima Wisam Ahmad entitled, “Healthcare Supply Chain Disruption Risks”, submitted in December 2022. Thesis advisor is Dr. Abdulrahim Shamayleh. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).